DESCRIPTIVE ANALYSIS OF THE TREASURES OF ISLAMIC SCHOOLS OF THOUGHT - Prayogi, Arditya; Nasrullah, Riki (Jurnal Studi Islam dan Sosial, 2024)
Currently, among Muslims there are various styles of schools of Islamic thought. The emergence of these various schools is a logical consequence of the process of understanding the main texts in the sources of Islamic law, namely the Al-Qur'an and As-Sunah (hadith) where there are rigid understandings of texts that do not provide room for discussion in them, as well as texts that loose text in the form of conjecture, which is possible to be interpreted in various ways. Thus, this article aims to provide a description of various schools of Islamic thought which are divided into four major schools. This article was written with a qualitative descriptive approach using the literature study method. From the results of the discussion, it is known that there are four major poles in Islamic thought, including Kalam, Philosophy, Fiqh and Sufism. These four major schools then have their own principles, methodologies and sources of interpretation, even though they all have the same basic foundation, namely the Al-Qur'an and As-Sunnah.